2021
DOI: 10.21307/jofnem-2021-079
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular characterization of Paratylenchus beltsvillensis n. sp. (Tylenchida: Paratylenchidae) from the rhizosphere of pine tree (Pinus virginiana Mill) in Maryland, USA

Abstract: The pin nematode, Paratylechus beltsvillensis n. sp. collected from rhizosphere soil of a Virginia pine tree (Pinus virginiana Mill) growing in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Forty-four sequences belonging to two nuclear rRNA and one mtRNA markers were generated in this study: 24 D2-D3, 9 18S, and 11 partial COI sequences. The results corroborate previous studies [5,6,8,42,[46][47][48] in finding the utility of this integrative approach and molecular data for species discrimination in Paratylenchus. Our findings are in accordance with the results of recent studies [5,6], since they showed that the D2-D3 of the 28S rRNA and the COI region within mtRNA were the most decisive, precise, and reliable molecular markers for discriminating among species and for the diagnosis at species level within Paratylenchus genus.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Forty-four sequences belonging to two nuclear rRNA and one mtRNA markers were generated in this study: 24 D2-D3, 9 18S, and 11 partial COI sequences. The results corroborate previous studies [5,6,8,42,[46][47][48] in finding the utility of this integrative approach and molecular data for species discrimination in Paratylenchus. Our findings are in accordance with the results of recent studies [5,6], since they showed that the D2-D3 of the 28S rRNA and the COI region within mtRNA were the most decisive, precise, and reliable molecular markers for discriminating among species and for the diagnosis at species level within Paratylenchus genus.…”
Section: Discussionsupporting
confidence: 91%
“…Members of the genus Paratylenchus Micoletzky, 1922 sensu lato, commonly known as pin nematodes, belong to the family Tylenchulidae Skarbilovich, 1947 (superfamily Criconematoidea Taylor, 1936 (Geraert, 1966); infraorder Tylenchomorpha De Ley & Blaxter, 2002; suborder Tylenchina Chitwood, 1950; order Rhabditida) [2][3][4]. According to morphological features and new molecular phylogenetic data [5][6][7][8], currently members belonging to Paratylenchus sensu lato are divided on two subgroups without taxonomic validity: (i) Paratylenchus species with a straight and short stylet, apparently the Iberian Peninsula were with Spanish populations of pin nematodes [5,6,38,40,41], with exception of Lima [43] and Macara [44]. To our knowledge, no previous studies of detailed descriptions included measurements and/or molecular characterizations of Portuguese populations of pin nematodes.…”
Section: Introductionmentioning
confidence: 99%
“…These clades are primarily equivalent with previous studies on Paratylenchus spp. phylogeny [ 3 , 4 , 5 , 6 , 9 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The newly obtained sequences of the D2-D3 expansion segments of the 28S rRNA, the ITS of the rRNA, and partial COI mtDNA genes were aligned using ClustalX 1.83 [91] with corresponding published gene sequences [13,14,23,24,26,30,[65][66][67]69,71,80,[92][93][94][95][96][97]. Outgroup taxa for each dataset were chosen based on previously published data [30].…”
Section: Phylogenetic and Sequence Analysismentioning
confidence: 99%